HOTAIR inhibited intracellular Ca2+ via regulation of Cav1.2 channel in human cardiomyocytes - Tan, W L; Xu, M; Liu, Z; Wu, T Y; Yang, Y; Luo, J; Yang, J; Luo, Y (Cellular and Molecular Biology, 2015)
HOTAIR, a long non”coding RNA (lncRNA), is reported to regulate chromatin organization and promote tumor progression. However, little is known about the roles of this gene in the modulation of calcium homeostasis in human cardiomyocytes. In the present study, we demonstrated that up”regulation of HOTAIR could suppress the expression of CaV1.2 in human cardiomyocytes. However, HOTAIR knockdown promoted CaV1.2 expression in human cardiomyocytes. In addition, we found that HOTAIR overexpression significantly reduced the intracellular Ca2+ contents; while knockdown of HOTAIR enhanced the Ca2+ contents in the cardiomyocytes. Moreover, enforced expression of CaV1.2 increased the calcium level in cardiomyocytes overexpressing HOTAIR. down”regulation of HOTAIR and up”regulation of CaV1.2 further enhanced the Ca2+ contents in the cardiomyocytes Taken together, these results for the first time demonstrate that HOTAIR inhibited the intracellular Ca2+ via regulation of CaV1.2 in human cardiomyocytes.